The effect of maternal position on venous return for pregnant women during MRI. (21st January 2021) - Hughes, Emer J.; Price, Anthony N.; McCabe, Laura; Hiscocks, Suzanne; Waite, Lara; Green, Elaine; Hutter, Jana; Pegoretti, Kelly; Cordero‐Grande, Lucilio; Edwards, Anthony David; Hajnal, Joseph V.; Rutherford, Mary A.
Abstract : Magnetic resonance imaging (MRI) in pregnancy is commonly undertaken in the left lateral tilt (LLT) position to prevent inferior vena cava (IVC) compression and supine hypotensive events, although this may be suboptimal for image quality. The supine position may also have an adverse effect on fetal well‐being. The spinal venous plexus may provide an alternative pathway for venous return in the presence of IVC compression. This study assesses morphology and blood flow of the IVC and spinal venous plexus for pregnant women in LLT and supine positions to ascertain the effect of maternal position on venous return during MRI. Eighty‐two pregnant women underwent phase contrast MRI (PC‐MRI) of the IVC and spinal venous plexus in the supine position; 25 were also imaged in the LLT position. Differences in life monitoring, IVC, spinal venous plexus and total venous return between the two positions were assessed. A linear regression assessed the relationship between flow in the IVC and the spinal venous plexus in the supine position. Increasing gestational age and the right‐sided position of the uterus on IVC and spinal venous plexus venous return were also evaluated. Hypotension symptoms were similar in supine (10%) and LLT (8%) positioning. Supine positioning decreased IVC height ( p < 0.004) and flow ( p = 0.045) but flow in the spinal venous plexus increased ( p < 0.001) compared with the LLT position. Total venous return showed no difference ( p = 0.989) between the two positions. Additional measurements of flow in the aorta also showed no significant difference between the two groups ( p = 0.866). Reduced IVC flow in the supine position was associated with increasing gestational age ( p = 0.004) and degree of right‐sided uterine position ( p = 0.004). Women in the left lateral decubitus position who then rotated supine had greater flow in the IVC ( p = 0.008) and spinal venous plexus ( p = 0.029) than those who started supine. For the majority of women, the spinal venous plexus acts as a complementary venous return system for pregnant women in the supine position, maintaining vascular homeostasis. Further study is needed to assess the effects on the health of the fetus. Abstract : This study assesses morphology and blood flow of the inferior vena cava (IVC) and spinal venous plexus for pregnant women in the left lateral tilt (LLT) and supine positions using phase contrast MRI. Supine positioning decreased IVC height and flow but flow in the spinal venous plexus increased compared with the LLT position. Total venous return showed no difference between the two positions. The spinal venous plexus acts as a complementary venous return system in the supine position during pregnancy.